Internally displaced persons: towards an effective international legal protection regime - Ngugi, Elias Lema (Department of Public Law, 2026)
Internal displacement has emerged as one of the great human tragedies of our time. It has also created an unprecedented challenge for the international community: to find ways to respond to what is essentially an internal crisis…protection should be central to the international response and [with] assistance should be provided in a comprehensive way that brings together the humanitarian, human rights, and development components of the United Nations.